The toxicogenic effect of Terminalia phanerophlebia Engl. & Diels leaf extract on oxidative stress parameters in an in vitro Hek293 model - Marcilyn R. Nyahada; Daniel G. Amoako; Anou M. Somboro; Isaiah Arhin; Hezekiel M. Khumalo; Rene B. Khan (GarVal Editorial Ltda., 2021)
Context: Medicinal plants are a highly sought-after alternative to current pharmaceutical drugs because they can be locally cultivated, inexpensive and possess minimal adverse effects. Given that Terminalia phanerophlebia (TP) possesses many useful properties and plays a role in modulating lethal diseases, the cytotoxic effect should be evaluated before its application for therapeutic use. Aims: To investigate the oxidative effect and molecular mechanisms of TP on human embryonic kidney (HEK293) cells. Methods: 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and adenosine triphosphate (ATP) assays were used to determine the cell viability whilst the thiobarbituric acid reactive species (TBARS) assay was used to detect lipid peroxidation. Endogenous antioxidants, catalase, superoxide dismutase, glutathione peroxidase, heat shock protein 70 and nuclear factor erythroid 2-related factor 2 (Nrf2), were used as oxidative stress markers and were detected via western blotting. Results: A decrease in cell viability with an IC50 of 1.36 mg/mL and ATP were noted. The concentration of malondialdehyde (MDA) increased significantly (p<0.005). Superoxide dismutase, Nrf2 and heat shock protein concentrations were increased. However, glutathione, glutathione peroxidase and catalase were depleted. Conclusions: The results obtained suggest that Terminalia phanerophlebia extract is toxicogenic and induced oxidative stress in HEK293 cells.